Social Reform, Modernization and Technical Diplomacy The ILO Contribution to Development (1930-1946) - Plata-Stenger, Véronique (Work in Global and Historical Perspective, 2020)
Based on an extensive exploitation of the ILO archives, this book analyzes the emergence of a development discourse and practices at the international level between 1930 and 1946. It challenges several presumptions with regard to the chronology of development and its ideological origins. By focusing on the actors and practices of development, this book offers new depth to the concepts of "epistemic communities" and "experts".